Dampak Program Qordhul Hasan BPR Syariah Mitra Mentari Sejahtera Terhadap Pertumbuhan Usaha Mikro Kader Pemuda Muhammadiyah Ponorogo: - - Anton Bawono; Raden Lukman Fauroni; Agus Supatma (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
The Qordhul Hasan program is a form of social financing provided by Islamic banking, aimed at encouraging community economic empowerment, particularly for micro-entrepreneurs. This article aims to analyze the impact of the Qordhul Hasan program provided by BPR Syariah Mitra Mentari Sejahtera Ponorogo on the development of micro-enterprises of Muhammadiyah Youth cadres. This research uses a literature review method with a descriptive-analytical approach, analyzing previous research findings, statistical data on small and medium enterprises, and Islamic micro-financing practices. The results indicate that Qordhul Hasan financing significantly contributes to increasing the capital, income, and sustainability of Muhammadiyah Youth cadres' micro-enterprises, although it still faces several challenges in terms of funding sources and business mentoring.